Using Scanning Strategy to Improve Students’ Reading Comprehension of the Second Grade of SMP Negeri 4 Minas - Khairina, Sadiatul; ', Syafri K; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to know whether scanning strategy can improve the reading comprehension ability of the second grade students of SMP Negeri 4 Minas and to find out what factors that improve the students’ reading comprehension ability. .Twenty one eight grade students participated in this study. The data were collected from several sources; observation sheet, reading comprehension tests, and field notes. The findings of this studyindicated that the application of using scanning strategy could improve students’ reading comprehension ability both at the cycle one and cycle two. The result of pre-test shows the average score of students reading comprehension ability was 59.4. It improved to 70.23 on the post-test 1 and 80 on the post-test 2. It was also proved that applying scanning strategy in comprehending narrative texts could improve students’ interest and motivation to read more after knowing how this strategy could help them collect the information needed from a text quickly and efficiently in the shortest period of time. Keywords: Scanning Strategy, Reading Comprehension